2017
DOI: 10.1111/cobi.12729
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of the pet trade on Indonesian birds

Abstract: The trade in wild animals involves one-third of the world's bird species and thousands of other vertebrate species. Although a few species are imperiled as a result of the wildlife trade, the lack of field studies makes it difficult to gauge how serious a threat it is to biodiversity. We used data on changes in bird abundances across space and time and information from trapper interviews to evaluate the effects of trapping wild birds for the pet trade in Sumatra, Indonesia. To analyze changes in bird abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 33 publications
0
102
0
3
Order By: Relevance
“…First, wildlife-rearing farms play key roles in supplying wildlife for markets. Similar to other areas in South Asia (Corlett, 2007;Li and Li, 1998;Harris et al, 2016), illegal wildlife hunting and trade for food, TCM and pet are widespread in South China, including in provinces such as Guangxi, Guang Dong and Hainan (Gong et al, 2006;Lee et al, 2004;Li, 1996, 1998;Liang et al, 2011;Zhou et al, 2005). Most illegal hunting activities are not for subsistence but rather for wildlife trade, because hunters can obtain high economic benefits from wildlife trade Li, 1996, 1998;Li et al, 2000;Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…First, wildlife-rearing farms play key roles in supplying wildlife for markets. Similar to other areas in South Asia (Corlett, 2007;Li and Li, 1998;Harris et al, 2016), illegal wildlife hunting and trade for food, TCM and pet are widespread in South China, including in provinces such as Guangxi, Guang Dong and Hainan (Gong et al, 2006;Lee et al, 2004;Li, 1996, 1998;Liang et al, 2011;Zhou et al, 2005). Most illegal hunting activities are not for subsistence but rather for wildlife trade, because hunters can obtain high economic benefits from wildlife trade Li, 1996, 1998;Li et al, 2000;Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
“…Several waterbird populations that have declined, including the Cinnamon Bittern (Ixobrychus cinnamomeus) and White-throated Kingfisher (Halcyon smyrnensis), may be partly due to the loss of wetland from construction of the farms. A more recent study revealed that pet trade was a significant predictor of bird species decline in Indonesia (Harris et al, 2016). More research is needed for understanding how wildlife-rearing farms are linked to the bird decline in Hainan Island.…”
Section: Discussionmentioning
confidence: 99%
“…; Harris et al . ). At the opposite end of the supply chain, markets where these species are sold are often the sources of introductions via deliberate or accidental releases (Carrete and Tella ).…”
mentioning
confidence: 97%
“…These particular preferences generate strong telecoupled legal and illegal wildlife trade flows that pose a challenge to the viability of wild populations. For instance, market prices in the pet trade were found to be a strong predictor of bird species declines in the wild in Indonesia (Harris et al 2016). These trading dynamics are also replicated across agricultural and forestry commodities, typically between high-income importers and low-income exporters (e.g., Exporter 1 and Importer 1 in Fig.…”
Section: Figmentioning
confidence: 85%